ANALISIS DISPARITAS PENDAPATAN PER KAPITA DENGAN PENDEKATAN SEKTORAL ANTAR WILAYAH KEDUNGSEPUR TAHUN 2010-2017 - Eka Mayang Sanditia; Whinarko Juliprijanto; Rusmijati . (DINAMIC : Directory Journal of Economic, 2019)
The government encourages every Regency/City to cooperate between district/regions in order to increase its competitiveness in the global economy. In Central Java there are several regional collaborations which have been formed, one of which is the collaboration of Kedungsepur region. However, this collaboration has differences in income between Kedungsepur region as evidenced by the high differences in per capita income between regencies/municipalities. This study aims to find out how much the per capita income disparity between the Regency/City regions of Kedungsepur region and any sectors that cause disparity in per capita income. The analytical method used in this study is the Williamson Index and Location Quotient. Based on the results of the Williamson Index analysis, the per capita income disparity between Kedungsepur regions from 2010-2017 has a tendency to increase with an average per capita income disparity of 0.8368 and a high per capita income disparity due to more than 0.5. Based on the Location Quotient analysis shows that there are 9 economic sectors that result in per capita income disparity in the Kedungsepur region.